Graphene‐Based Textiles for Thermal Management and Flame Retardancy. (3rd August 2022) - Ge, Qi; Chu, Jingwen; Cao, Weiqi; Yi, Fenglian; Ran, Zhou; Jin, Zhan; Mao, Boyang; Li, Zheling; Novoselov, Kostya S.
Abstract: Textile thermoregulation and thermal protection are crucial for human health and safety. Individual thermophysiological comfort control and flame retardancy are lacking in traditional garments. Novel nanomaterial innovations have solved these limitations and have facilitated the development of next‐generation intelligent textiles. Smart textiles based on graphene and graphene derivatives material have attracted substantial attention owing to its superior electrical conductivity, high thermal conductivity, and flexibility. This review provides an overview of the current progress on the smart textiles using graphene and graphene derivative material with a focus on personal thermal management and flame retardancy. It covers mechanics, material developments, fabric designs, and on‐body applications, offering a comprehensive knowledge and scope of the entire area. Innovations in chemistry and materials with worldwide collaboration will push the frontiers of graphene‐based smart textiles, promoting the development of genuine commercial goods on the market. Abstract : Personal thermal management and fire retardancy are the two important aspects of next generation smart textiles, and graphene and its derivatives have the capability to enable both of them. It this review, it is provided an overview of the current progress in this field, and some critical thoughts and perspectives for future studies.